2010
DOI: 10.1111/j.1365-2699.2009.02216.x
|View full text |Cite
|
Sign up to set email alerts
|

Body size–climate relationships of European spiders

Abstract: Aim  Geographic body size patterns of mammals and birds can be partly understood under the framework of Bergmann’s rule. Climatic influences on body size of invertebrates, however, appear highly variable and lack a comparable, generally applicable theoretical framework. We derived predictions for body size–climate relationships for spiders from the literature and tested them using three datasets of variable spatial extent and grain. Location  Europe. Methods  To distinguish climate from space, we compared clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
87
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 36 publications
7
87
2
Order By: Relevance
“…Therefore, smaller spiders should occur in more humid habitats, which very often means more dense vegetation. Such regularity was observed by Entling et al (2010) when taking into consideration the mean body size for whole assemblages based on the size of particular species [12]. They revealed that the mean body size of spider species in Europe decreases from warm and dry to cool and moist environments.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Therefore, smaller spiders should occur in more humid habitats, which very often means more dense vegetation. Such regularity was observed by Entling et al (2010) when taking into consideration the mean body size for whole assemblages based on the size of particular species [12]. They revealed that the mean body size of spider species in Europe decreases from warm and dry to cool and moist environments.…”
Section: Discussionsupporting
confidence: 57%
“…Current knowledge of mechanisms affecting the body size distribution is based mainly on studies involving vertebrates [6][7][8][9], while researches on invertebrates are still rare, although more frequent during last years [10][11][12][13][14][15]. Many of these studies analysed body size patterns of a particular group of invertebrates on a large geographical scale like a continent [10,[12][13][14], whereas knowledge about mechanisms affecting body size distribution on a local scale are still limited [11,[16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, the habitats of the species had a significantly high air temperature and solar radiation, and a low relative humidity reflecting comparatively warm, dry environments. In terrestrial arthropods the body size of ants has been shown to decrease with temperature whereas bees, butterflies and moths show a variety of body size-climate patterns (Entling et al 2010). In tiger beetles large body size has been associated with coastal and reservoir habitats with high wind speed, low soil moisture and high soil pH, while species with small body have been associated with riverine habitats with low wind speed, high soil moisture and low soil pH (Dangalle et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge here that our justification for using these three variables is a simplistic way of testing the above hypotheses and a thorough investigation might consider other macroclimatic variables and/or combinations of variables. Moreover, there are other hypotheses on body size patterns for ectotherms (e.g., Table 1 in Entling et al 2010) and so we make no claims for completeness. However, we note that the main purpose of this work was to examine the relative performance of topoclimatic variables over macroclimatic variables, the latter of which are commonly used for testing body-size clines (e.g., Harris et al 2012).…”
Section: Climate Datamentioning
confidence: 99%